BUSINESS SUPPORT IN SUPERMARKETS: ANALYSIS UNDER THE PERSPECTIVE OF ITS OWNERS - Casagrande, Jacir Leonir; Elias, Leandro Medeiros; Sehnem, Simone (Contextus - Revista Contemporânea de Economia e Gestão, 2014)
Nowadays, apart from the commercialization of products, the Supermarkets provide satisfaction to customers. It is also very common to find third-party stores and services added. In this context, the objective of this study is to analyze how the administrative management of these stores and services, also called Support Businesses, is carried out by a network of supermarkets in the state of Santa Catarina. A network of 12 establishments, which serves 57,000 customers per day in the state of Santa Catarina and considering 170 Support Businesses, participated in this study. Thus, the researchers administered a questionnaire to 130 owners of those Businesses in the following cities of Santa Catarina: Florianópolis, São José, Criciúma, Palhoça, Blumenau and Joinville. Based on the collected data, it was evident that there is a lack of professional management for this new reality of supermarkets. Therefore, this empirical-exploratory article contributes to the beginning of a new theory about an administrative management for these businesses. This articles ends with an administrative management proposal that contemplates the ambitions of the owners of stores and services installed in supermarkets.